Recent trends (2010-2018) in traumatic brain injury in Greece: Results on 2042 patients. Issue 9 (September 2020) - Stranjalis, George; Komaitis, Spyridon; Kalyvas, Aristotelis V.; Drosos, Evangelos; Stavrinou, Lampis C.; Koutsarnakis, Christos; Kalamatianos, Theodosis
Highlights: TBI-related admissions at the largest neurosurgical department in Greece during the largest part of the past decade were analyzed. The present results indicate increases in the contribution of fall-related geriatric injury to TBI-related admissions and in-hospital mortality. The results indicate the need for fall prevention strategies. Abstract: Background: Recent analysis on the epidemiology of traumatic brain injury (TBI) within Europe indicates an increase in fall-related injuries and in the incidence of hospitalization among older adults as well as a decrease in contribution of road traffic accidents (RTA). Given the paucity of recent national data, we analyzed TBI-related admissions from the Athens Head Trauma Registry during the largest part of the past decade (2010-2018), a period marked by a profound national socioeconomic crisis. Methods: Demographic and clinical data of admitted TBI patients were collected and analyzed statistically. Results: The mean age of patients (N=2042, 68% men) was 59 years (median 64 years). Patient age showed an upward trend across the study period. Most cases were mild, while moderate and severe injuries were indicated in, 11% and 20%, respectively. Falls were the predominant cause of injury (46% of cases), followed by RTA (38%). An upward trend in the frequency of fall-related injury was apparent across the study period; RTA-related injury frequency displayed a downward trend during the second part of the study period. Assault-related injury accounted for 6%. Surgery took place in 11% of cases. In-hospital mortality (IHM) was 21%. Fall-related mortality contributed to 56% of total IHM; RTA-related mortality contributed to 30%. The mean length of hospital stay was 13 days (median: 5 days). Conclusions: The present findings suggest a shift in the epidemiologic profile of TBI patients in Greece with a rise in the proportion of elderly patients, a concomitant increase in fall-related injuries and a reduction in RTA-related injury. They also highlight fall-related injury as the predominant cause of IHM. Our results point towards the urgent need for the intensification of fall prevention strategies, continuing medical education as well as public information campaigns on the risks of geriatric fall-related injury.